1993
DOI: 10.1002/bjs.1800800746
|View full text |Cite
|
Sign up to set email alerts
|

Safety of double-stapled anastomosis in low anterior resection

Abstract: Clinical leakage of the anastomosis follows low anterior resection for rectal carcinoma in 5-10 per cent of patients despite standard stapling techniques. A modification of this method has obviated the need for a distal purse string. A flexible transverse stapling instrument (Roticulator 55) is applied across the rectum below the tumour, and a double-staggered row of staples is inserted as a substitute for the distal purse string. End-to-end stapled anastomosis is then performed with peranal insertion of a Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 10 publications
0
27
0
1
Order By: Relevance
“…Additionally, there was no local recurrence during the 26.8-mo follow-up period, although the long-term survival rate is unknown. This double stapling technique was first introduced in colorectal surgery (particularly rectal cancer) for use in a narrow operative field, and its safety in colorectal surgery has already been reported and demonstrated in many studies [26][27][28][29] . Thus, the double stapling technique can be useful and time-saving for esophagojejunostomy after LTG, and recent studies have reported on its safety [23,30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there was no local recurrence during the 26.8-mo follow-up period, although the long-term survival rate is unknown. This double stapling technique was first introduced in colorectal surgery (particularly rectal cancer) for use in a narrow operative field, and its safety in colorectal surgery has already been reported and demonstrated in many studies [26][27][28][29] . Thus, the double stapling technique can be useful and time-saving for esophagojejunostomy after LTG, and recent studies have reported on its safety [23,30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…After its initial introduction by Nance in 1979 [6], the doublestapling method has been repeatedly reported as a safe and effective procedure for lower anterior resections [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features that were frequently cited included: signs of localised or generalised peritonitis; faecal discharge from the wound and/or drain; abscess; purulent discharge from drain, wound or anus; and fever. Some studies defined a clinical anastomotic leak as that requiring re-operation, 258,259 while others accepted signs of leak without further surgery.…”
Section: Studies Of Lower Gastrointestinal Surgerymentioning
confidence: 99%
“…258 Some studies defined a clinical anastomotic leak as that requiring re-operation, 258,259 while others accepted signs of leak without further surgery. This was also true of the upper gastrointestinal and hepatopancreaticobiliary literature, where some authors accepted clinical features (e.g.…”
Section: Clinical Assessment Of Lower Gastrointestinal Anastomotic Leakmentioning
confidence: 99%